Weather Index Insurance and Shock Coping : Evidence from Mexico's CADENA Program - de Janvry, Alain; Ramirez Ritchie, Elizabeth; Sadoulet, Elisabeth (World Bank, Washington, DC, 2016)
Weather risk and incomplete insurance markets are significant contributors to poverty for rural households in developing countries. Weather index insurance has emerged as a possible tool for overcoming these challenges. This paper provides evidence on the impact of weather index insurance from a pioneering, large-scale insurance program in Mexico. The focus of this analysis is on the ex-post effects of insurance payments. A regression discontinuity design provides find evidence that payments from weather index insurance allow farmers to cultivate a larger land area in the season following a weather shock. Households in municipalities receiving payment also appear to have larger per capita expenditures and income in the subsequent year, although there is suggestive evidence that some of this increase is offset by a decrease in remittances. While the cost of insurance appears to be high relative to the payouts, the benefits exceed the costs for a substantial range of outcomes.